ANALISIS PENERAPAN KURIKULUM 2013 DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Mirnasulistyawati Mirnasulistyawati; Armelia Armelia; Afdal Afdal (JURNAL MAPPESONA, 2020)
Indonesia is a country that always try to follow the development of Global Era and persuasion, every change of Head of State (President) also Change of Education Minister of Curriculum Change was done. Problems encountered are, Curriculum in Indonesia has undergone several changes, until finally the new curriculum was born in 2013 which is a curriculum based on competence and character In accordance with the problem, this study aims to analyze "How Application of Curriculum 2013 in Improving the Quality of Learning". The method used is by using descriptive method to know the planning and implementation of curriculum 2013 conducted by teachers in the implementation and improvement of learning.